2018
DOI: 10.1182/blood-2017-07-794875
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl 4-hydroxylase 2 promotes B-cell lymphoma progression via hydroxylation of Carabin

Abstract: B-cell lymphomas are heterogeneous blood disorders with limited therapeutic options, largely because of their propensity to relapse and become refractory to treatments. Carabin, a key suppressor of B-cell receptor signaling and proliferation, is inactivated in B-cell lymphoma by unknown mechanisms. Here, we identify prolyl 4-hydroxylase 2 (P4HA2) as a specific proline hydroxylase of Carabin. Carabin hydroxylation leads to its proteasomal degradation, thereby activating the Ras/extracellular signal-regulated ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
6
27
0
Order By: Relevance
“…Our GSEA indicated that TBC1D10C6 regulated the KRAS-signaling pathway, which is consistent with the existing research (33). Moreover, ssGSEA revealed that TBC1D10C has a high positive correlation with B cells and T cells, which is consistent with the research of Jiang et al (31) but contradicts Schickel et al (32). The opposing results may be due to study differences, one focused on lymphoid disease while the other was interested in myocardial disease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our GSEA indicated that TBC1D10C6 regulated the KRAS-signaling pathway, which is consistent with the existing research (33). Moreover, ssGSEA revealed that TBC1D10C has a high positive correlation with B cells and T cells, which is consistent with the research of Jiang et al (31) but contradicts Schickel et al (32). The opposing results may be due to study differences, one focused on lymphoid disease while the other was interested in myocardial disease.…”
Section: Discussionsupporting
confidence: 88%
“…GTPase-activating protein (31). Moreover, TBC1D10C physically interacts with CaN T cells and H-Ras in addition to inhibiting Ras/MAPK signaling (31,32). Our GSEA indicated that TBC1D10C6 regulated the KRAS-signaling pathway, which is consistent with the existing research (33).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the family of collagen prolyl 4-hydroxylases (P4HAs) has been found to be overexpressed in multiple cancers, promoting cancer progression and is associated with poor clinical outcomes 57,58 . The inhibition of collagen prolyl 4-hydroxylases has been suggested as a strategy to reduce invasiveness of breast cancer 57 and B-cell lymphoma 59 however it remains an unexplored strategy in OS. The primary function of LOX is catalyzing crosslinking of collagens in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…There is more evidence shown that PHD2 silencing in cancer cells can exert both pro-and antitumoral effects, depending on the cellular context. On the one hand, PHD2 promotes metastasis through activation of CAFs and inactive PHD2 inhibits proliferation and growth in breast cancer [82], stroma and bone marrow-derived cells [83], lung carcinoma [84], B-cell lymphomas [85], hepatocellular carcinoma [86], and head and neck squamous cell carcinoma [87]. On the other hand, there is some evidence for the antitumoral effect of PHD2 in gastric adenocarcinoma [87], non-small-cell lung cancer [87], and prostate cancer [88].…”
Section: Physical and Chemical Characteristics Of Tmementioning
confidence: 99%